2016
DOI: 10.52964/amja.0634
|View full text |Cite
|
Sign up to set email alerts
|

Improving acute care for older people at scale – the Acute Frailty Network

Abstract: Older people form a growing proportion and volume of those accessing urgent care. Non-specific presentations, multiple comorbidities and functional decline make assessment and management of this cohort challenging. Comprehensive Geriatric Assessment offers an evidence based framework to assess and mange older people, especially those with frailty. In this article we describe the CGA approach, underpinned by specific examples illustrating some of the key competencies required, and describe the role of the Acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Two studies have demonstrated that frailty indices are predictive of short- 6 and long-term mortality 7 and hospital length of stay (LOS) 6 following hip fracture, but neither study examined whether frailty measures predict other clinically important outcomes associated with hip fracture, such as complications or institutionalization. In recent years, particularly in the UK due to the efforts of the Acute Frailty Network, 8 there has been widespread adoption of the Clinical Frailty Scale (CFS) in all older patients admitted to hospital. The CFS is an assessment of a patient’s frailty status based on the two weeks prior to their admission, and is only validated in those above the age of 65.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have demonstrated that frailty indices are predictive of short- 6 and long-term mortality 7 and hospital length of stay (LOS) 6 following hip fracture, but neither study examined whether frailty measures predict other clinically important outcomes associated with hip fracture, such as complications or institutionalization. In recent years, particularly in the UK due to the efforts of the Acute Frailty Network, 8 there has been widespread adoption of the Clinical Frailty Scale (CFS) in all older patients admitted to hospital. The CFS is an assessment of a patient’s frailty status based on the two weeks prior to their admission, and is only validated in those above the age of 65.…”
Section: Introductionmentioning
confidence: 99%
“…Forty-six statements were developed on healthcare structures, processes and desired outcomes, with consensus defined at ≥ 80% agreement This was a consensus-based study and as such it sought to explore consensus in relation to the Donabedian approach of structure, process and outcome. The focus of the statements included; strategic development, change management and indicator measure and awareness raising for implementation Country: European Union Participants: Five members from each country (n = 28), giving 140 members The five included: one policy maker, two healthcare commissioners, one healthcare provider director level and one clinician (physician or pharmacist) Consensus was obtained for statements relating to: potential gain arising from polypharmacy management (3/4 statements); strategic development (7/7); change management (5/7) indicator measures (4/6); legislation (0/3); awareness raising (5/5); polypharmacy reviews (5/7); and EU vision (0/7) Not relevant for this paper Conroy et al [ 30 ] Improving acute care for older people at scale - The Acute Frailty Network (AFN) This descriptive paper covers different approaches used to achieve high quality care for frail older people with urgent care needs. The evidence base is summarized and the paper described how the Acute Frailty Network has set about delivering improvements at scale The AFN was designed using the Breakthrough Series Collaborative (BTS) approach, involving health and social care systems working with support by national clinical and improvement experts and sharing experiences through national networking events.…”
Section: Resultsmentioning
confidence: 99%
“…Two papers provided detailed descriptions of the characteristics of programs that addressed the care of frail older people but did not carry out data collection [ 30 , 31 ]. In terms of research design, the other 6 papers [ 17 , 26 29 , 32 ] mainly used qualitative methods including: interviews [ 17 , 27 , 28 ], focus groups [ 17 , 26 , 27 ] and Delphi consensus [ 29 ] and workshops [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations